2018
DOI: 10.4136/ambi-agua.2201
|View full text |Cite
|
Sign up to set email alerts
|

Water quality of springs in areas under different land uses in the southern highlands of Santa Catarina

Abstract: This study sought to characterize the conditions of springs used for domestic consumption and to analyze their water quality. The springs are situated in catchment areas (drainage areas) with different soil uses in rural properties of the southern plateau of Santa Catarina, Brazil. To this end, 56 springs used to supply rural properties were selected in the counties of Lages, Otacílio Costa, São José do Cerrito, Painel, and Bocaina do Sul. The water catchment area of the springs were described in detail with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
(11 reference statements)
3
5
0
2
Order By: Relevance
“…For deep wells, there were samples with pH above 10, which is related to geologic characteristics of the aquifer (ABAS, 2020). Oliveira and Galvão (2019), in deep well waters, corroborate with the here presented study and indicated that pH values are in the neutral band and according to the current Brazilian and WHO guidelines (Ramos et al, 2018;Portal et al, 2019).…”
Section: Water Qualitysupporting
confidence: 91%
See 2 more Smart Citations
“…For deep wells, there were samples with pH above 10, which is related to geologic characteristics of the aquifer (ABAS, 2020). Oliveira and Galvão (2019), in deep well waters, corroborate with the here presented study and indicated that pH values are in the neutral band and according to the current Brazilian and WHO guidelines (Ramos et al, 2018;Portal et al, 2019).…”
Section: Water Qualitysupporting
confidence: 91%
“…The electrical conductivity values are similar to those found by Ramos et al (2018) and Dragon (2021). Eletrical condutivity values may have a connection with soil characteristics and geological structure.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…According to Alves and coauthors [31], water contaminations can occur due to failures in the public collection system, also because of the bad hygiene and maintenance of the water reservoir. In countryside area there is a lack of treatment and protection of artesian wells, streams, rivers and dams [32]. As well as to the Brazilian regulations, the samples were not conformed in the United States legislation, which states that total coliforms should not surpass the limit of 5 % from total samples analyzed in a month [33].…”
Section: Discussionmentioning
confidence: 99%
“…As nascentes de cursos de água são resultantes de afloramentos do lençol freático, ou são oriundas de aquíferos artesianos, e têm sido utilizadas com frequência para o consumo humano, dessedentação animal e para a irrigação de cultivos agrícolas de pequenas comunidades. Têm uma enorme importância para o abastecimento humano, como também para a formação e manutenção dos cursos d'águas e, consequentemente para as bacias hidrográficas (Kløve et al, 2011;Davis et al, 2017;Ramos et al, 2018;Sun et al, 2019). No entanto, essas importantes fontes hídricas, não raro, sofrem sérios problemas de degradação, devido, dentre outros, às alterações dos regimes do fluxo d'água por conta do uso desenfreado do solo para a agricultura e para a expansão urbana, sem o planejamento adequado (Kløve et al, 2014).…”
Section: Introductionunclassified